Protective environmental factors for neuromyelitis optica - Graves, Jennifer (Neurology, 2014)
OBJECTIVE: To determine whether early environmental factors, such as cesarean delivery, breastfeeding, and exposure to smoking or herpes viruses, are associated with neuromyelitis optica (NMO) risk in children. METHODS: This is a case-control study of pediatric NMO, multiple sclerosis (MS), and healthy subjects. Early-life exposures were obtained by standardized questionnaire. Epstein-Barr virus, cytomegalovirus, and herpes simplex virus 1 antibody responses were determined by ELISA. Multivariate logistic regression models were used to adjust for age at sampling, sex, race, and ethnicity. RESULTS: Early-life exposures were obtained from 36 pediatric subjects with NMO, 491 with MS, and 224 healthy controls. Daycare (odds ratio [OR] 0.33, 95% confidence interval [CI] 0.14, 0.78; p < 0.01) and breastfeeding (OR 0.42, 95% CI 0.18, 0.99; p = 0.05) were associated with lower odds of having NMO compared with healthy subjects. Cesarean delivery tended to be associated with 2-fold-higher odds of NMO compared with having MS/clinically isolated syndrome (OR 1.98, 95% CI 0.88, 4.59; p = 0.12) or with being healthy (OR 1.95, 95% CI 0.81, 4.71; p = 0.14). Sera and DNA were available for 31 subjects with NMO, 189 with MS, and 94 healthy controls. Epstein-Barr virus, herpes simplex virus 1, cytomegalovirus exposure, and being HLA-DRB1*15 positive were not associated with odds of having NMO compared with healthy subjects. CONCLUSIONS: Exposure to other young children may be an early protective factor against the development of NMO, as previously reported for MS, consistent with the hypothesis that infections contribute to disease risk modification. Unlike MS, pediatric NMO does not appear to be associated with exposures to common herpes viruses.